The Role of TikTok and Instagram Social Media in Strengthening Gen Z Citizenship Identity - Indah Sari; Nurul Zuriah; Rose Fitria Lutfiana (FKIP - Universitas Riau, 2026)
TikTok and Instagram social media have become interactive spaces in the lives of Generation Z. Platform use influences how communicate, obtain information, and learn non-formally, there impact's digital citizenship identity. This study aims to analyze the level of TikTok and Instagram usage, measure relationship between social media usage and digital citizenship identity, and strengthen the role of digital citizenship identity in students. The study used mixed-methods approach with sequential explanation strategy. Quantitative data were obtained through questionnaires distributed to 120 students, while qualitative data were collected through interviews to deepen the results. The findings indicate that TikTok and Instagram usage are in the high category. Spearman's correlation test showed a significant relationship between social media usage and students' digital citizenship identity (r = 0.433; p < 0.05). Qualitative findings confirm that TikTok and Instagram social media content plays a role in increasing civic literacy, tolerance, and national awareness. The study's conclusions indicate that TikTok and Instagram have an important role in strengthening Generation Z's digital citizenship identity, especially when used positively and selectively, and when they support national values. This study also encourages the development of educational content on social media for civic learning.